2019
DOI: 10.1039/c9cp01916b
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast flavin/tryptophan radical pair kinetics in a magnetically sensitive artificial protein

Abstract: Flavin/tryptophan radical pairs in artificial proteins demonstrate that singlet- and triplet-born pairs can be exploited as biological magnetic sensors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 50 publications
1
17
0
Order By: Relevance
“…While flavins usually show ISC on a ns time scale, [10,26a] the deprotonated forms converts on the order of 100 ps, [26b] still being longer than the observed time range of 1 ps. In contrast, non‐specific ET is driven via an edge‐to‐edge tunneling for short distances within 25 ps or shorter, depending on the ion contact pair distance [26c] . Therefore, ultrafast non‐specific ET can be a competing pathway to direct ET with Trp.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While flavins usually show ISC on a ns time scale, [10,26a] the deprotonated forms converts on the order of 100 ps, [26b] still being longer than the observed time range of 1 ps. In contrast, non‐specific ET is driven via an edge‐to‐edge tunneling for short distances within 25 ps or shorter, depending on the ion contact pair distance [26c] . Therefore, ultrafast non‐specific ET can be a competing pathway to direct ET with Trp.…”
Section: Resultsmentioning
confidence: 99%
“…The ET from Trp to the flavin moiety and the formation of the hydroquinone forms FlavinH − and FlavinH − 2 by non‐specific ET are competitive pathways. Since the latter formation involves a ion pair state, [26c] the reference system PR shows a dominant non‐specific ET whereas P0a has a weak non‐specific ET (cf. a weak band at 470 nm) and therefore a strengthened and directed ET.…”
Section: Discussionmentioning
confidence: 99%
“…The dramatic τ T reduction observed for Q50W can be attributed to electron transfer processes involving the tryptophan and 3 FMN moieties, including the formation of radical pairs. 16,17 Conversely, Q50E resembled the WT displaying a 3 FMN decay of 31 μs. The lifetime values obtained in this work for WT and Q103V are consistent with data previously reported.…”
Section: Q103mentioning
confidence: 94%
“…14,18 For the latter instead, the generation of FMN •-/Trp •+ radical pairs and back electron transfer processes may explain the low intensity of the 600-nm band, as well as the shorter 3 FMN* lifetime observed by transient absorption. 17 Notably, circular dichroism spectra of light-irradiated mSOG variants showed that formation of the FMN radical did not cause major changes in the protein structure ( Figure S8).…”
Section: Q103mentioning
confidence: 95%
“…From this perspective, nonstatic magnetic field sensitivity would not be an evolutionary capacity driven by seismic events, but a collateral/derived capacity consisting of a lowered response threshold. To explain the biological effects of weak magnetic fields, some molecular transduction mechanisms have been proposed (Binhi and Prato 2018;Bialas et al, 2019). While for animal navigation/orientation, the main hypothesis is a specialized magnetic sense associated with pairs of radicals located in the retina of the eye, nonspecific effects could occur due to the interaction of magnetic fields with the magnetic moments of rotating molecules dispersed in the organism.…”
Section: Reports On Earthquake Lightsmentioning
confidence: 99%